Easter bonnet murder - Meier, Leslie (Meier, Leslie. Lucy Stone mystery, 2022)
"Known for its cheerful staff and elaborate annual Easter Bonnet Contest, the Heritage House senior center regularly attracts new residents and positive press. But once the town's retired librarian, Miss Julia Tilley, checks in to recover from an illness, Lucy sees a side of the facility that isn't quite so perfect and pristine. And the place may soon be making headlines for different reasons following an unexplained disappearance ... Lucy can't fathom how Agnes Neal could go missing from assisted living over a silly Easter bonnet contest, or why few seem concerned as signs point to foul play. A retired journalist with an independent mind, Agnes had an eye for details and little interest in conforming to catty cliques or rules set by her caretakers--traits that threatened some and angered others ... While police stall the investigation without answers, Lucy realizes backstabbing has no age limit when alarming parallels bloom between her daughter's college frenemies and social circles at Heritage House. Gathering clues as flimsy as a half-eaten milk chocolate bunny, Lucy must discover what happened to Agnes--before her own story becomes another springtime tragedy left unsolved"--